Cloud-radiative effects on implied oceanic energy transports as simulated by atmospheric general circulation models - Gleckler, P. J.; Randall, D. A.; Boer, G. (Lawrence Livermore National Laboratory, 1994)
This paper reports on energy fluxes across the surface of the ocean as simulated by fifteen atmospheric general circulation models in which ocean surface temperatures and sea-ice boundaries are prescribed. The oceanic meridional energy transport that would be required to balance these surface fluxes is computed, and is shown to be critically sensitive to the radiative effects of clouds, to the extent that even the sign of the Southern Hemisphere ocean energy transport can be affected by the errors in simulated cloud-radiation interactions.